(3TQM fgL GdHdGZIs - (3CHhMGeO YRGdOjf YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjf Hf CHi GdMOjOs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3SYjO Hf UdGM Hf Ydi Hf eMeO Hf Ydi Hf efUhQ Hf MSf Hf jMji GdNhdGfi s)
(3ChdgG (B:s
(3hef cJGH dg Ydjg GdSdGe Edi Cgd GdHUQI(B: (3hbO cGf ef GfJTGQ NJdce hTbGbce s
(3BNQgG (B:s
(3hGf jUhf hLgi Yf GdeNdhbjf,hjca Yfi YGOjI GdXGdejfhHg Je GdcJGH s
(3GdeLdO GdGNjQs
(3egedI GdfbW GMjGfGs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs